Monetary policy, bank lending and corporate investment - Vithessonthi, Chaiporn *; Schwaninger, Markus; Muller, Matthias O (Elsevier, 2017)
The purpose of this study is to shed light on the chain of causality from macroeconomic financial policy to the microeconomic investment function. Concretely, we aim to provide an in-depth analysis of the relationships between the monetary policy of central banks, the loan policy of commercial banks, and the investment behavior of firms. We focus on countries that conduct their monetary policy under the inflation-targeting framework. Our empirical analysis with data from Germany, Switzerland and Thailand provides several new insights. First, after controlling for the US monetary policy, the monetary policy in Germany and Thailand appears to influence the banks’ lending rate in the short run (i.e. within two months), whereas the monetary policy in Switzerland seems to be ineffective at influencing the banks’ lending rate in the short run. Second, our results show that the banks’ lending rate has a negative effect on their loans and that this negative effect is weakened by their growth opportunities. Third, we find that the supply of bank loans plays a more pivotal role in determining firms’ investment than the lending rate. Last but not least, we document that neither the lending rate nor the loan-to-assets ratio moderates the sensitivity of the firms’ investment to growth opportunities